2022
DOI: 10.3389/fneur.2022.887818
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of serum neuron-specific enolase level to admission glasgow coma scale score is associated with diffuse axonal injury in patients with moderate to severe traumatic brain injury

Abstract: BackgroundModerate to severe traumatic brain injury (TBI) is frequently accompanied by diffuse axonal injury (DAI). Considering the low sensitivity of computed tomography (CT) examination for microbleeds and axonal damage, identification of DAI is difficult using conventional diagnostic methods in the acute phase. Neuron-specific enolase (NSE) has been demonstrated to be increased in serum following various types of TBI and is already clinically/commercially available. We conjecture that serum NSE level to adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Analysis of 228 patients with TBI showed that education status was correlated with MoCA scores: Those patients with higher level of education had significant association with higher MoCA scores ( p = 0.012) ( Panwar et al, 2019 ). Marshall CT score, pupillary light reflex, duration of coma and admission GCS were predictors of clinical outcome in DAI ( Palmieri et al, 2021 ; Xie et al, 2021 ; Chen et al, 2022 ). In the present study we also confirmed that return of consciousness, Marshall CT score, age and DAI grade have a negative correlation with cognitive function in DAI patients with 6-month GOSE 5–8.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Analysis of 228 patients with TBI showed that education status was correlated with MoCA scores: Those patients with higher level of education had significant association with higher MoCA scores ( p = 0.012) ( Panwar et al, 2019 ). Marshall CT score, pupillary light reflex, duration of coma and admission GCS were predictors of clinical outcome in DAI ( Palmieri et al, 2021 ; Xie et al, 2021 ; Chen et al, 2022 ). In the present study we also confirmed that return of consciousness, Marshall CT score, age and DAI grade have a negative correlation with cognitive function in DAI patients with 6-month GOSE 5–8.…”
Section: Discussionmentioning
confidence: 98%
“…DAI is caused by acceleration-deceleration or rotational forces on brain tissues, resulting in axonal shear injuries and delayed axonal disconnection, categorized as a special type of traumatic brain injury (TBI) ( Mu et al, 2021 ; Zhou et al, 2021 ; Chen et al, 2022 ; Kim et al, 2022 ). A total of 20–38% of TBI patients with DAI were followed up with unfavorable outcome (Extended Glasgow Outcome Scale, GOSE 1–4) ( Humble et al, 2018 ; Lohani et al, 2020 ), but over 85% suffered from persistent cognitive impairment ( Macruz et al, 2022 ; RaukolaLindblom et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We need to explore convenient collected, objective, and dynamically predictive indicators. Our previous studies have found that NGR at admission could be used as an independent predictor of DAI [7], so we further hypothesized that the dynamic changes in NGR can more accurately predict the long-term neurological function of DAI patients and provide support for disease assessment and treatment strategy.…”
Section: Introductionmentioning
confidence: 95%
“…If DAI can be diagnosed early after TBI and the long-term neurological function of these patients can be accurately predicted, appropriate treatment measures and early targeted rehabilitation programs can be given to DAI patients with a high probability of unfavorable outcome, which will be of great help in improving their prognosis [6][7][8]. Therefore, many scholars were committed to exploring prognosis assessment schemes for DAI.…”
Section: Introductionmentioning
confidence: 99%